Evaluation of EDM characteristics of synthesised AA2024-2 & 3 wt% SiO2 metal matrix nanocomposite (MMNC). (2020) - Kumar, Veneet; Singh, Bharat; Himanshu,; Chandel, Siddharth; Singhal, Piyush
Abstract: The present study is solely based upon the comparison of electric discharge machining (EDM) characteristics of AA2024 alloy and synthesised Aluminium metal matrix composite, fabricated with two different weight percentages of Silicon di-oxide (SiO2 ) as reinforcement. The experiment is performed using optimized critical parameters of EDM which affects the machining characteristics such as material removal rate (MRR), tool wear rate (TWR) and surface roughness (SR) considerably. In this study it is observed that after the reinforcement of SiO2 nano powder (30 nm) in aluminium metal matrix (AA2024), the material removal rate of developed metal matrix nanocomposite (MMNC) decreases whereas TWR and SR increase as compared to the base metal AA2024.